2019
DOI: 10.3390/ijms20061453
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Vitamin E as a Bone-Protecting Agent: A Review on Current Evidence

Abstract: Bone remodelling is a tightly-coordinated and lifelong process of replacing old damaged bone with newly-synthesized healthy bone. In the bone remodelling cycle, bone resorption is coupled with bone formation to maintain the bone volume and microarchitecture. This process is a result of communication between bone cells (osteoclasts, osteoblasts, and osteocytes) with paracrine and endocrine regulators, such as cytokines, reactive oxygen species, growth factors, and hormones. The essential signalling pathways res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 164 publications
0
56
1
Order By: Relevance
“…The capability of T3 in modulating inflammation has been extensively explored by researchers. T3 acts as regulator for the expression of pro-and anti-inflammatory mediators including TNF-α, IL-1, IL-2, IL-6, IL-8, IL-10, IL-23, IFN-γ, iNOS, and COX-2 [8,404]. The most implicated signal transduction pathways involved in orchestrating inflammatory response are NF-κB, MAPK, signal transducer and activator of transcription (STAT) and Toll-like receptor (TLR) signaling [8,405].…”
Section: Anti-inflammatory Properties Of Tocotrienolmentioning
confidence: 99%
See 2 more Smart Citations
“…The capability of T3 in modulating inflammation has been extensively explored by researchers. T3 acts as regulator for the expression of pro-and anti-inflammatory mediators including TNF-α, IL-1, IL-2, IL-6, IL-8, IL-10, IL-23, IFN-γ, iNOS, and COX-2 [8,404]. The most implicated signal transduction pathways involved in orchestrating inflammatory response are NF-κB, MAPK, signal transducer and activator of transcription (STAT) and Toll-like receptor (TLR) signaling [8,405].…”
Section: Anti-inflammatory Properties Of Tocotrienolmentioning
confidence: 99%
“…T3 acts as regulator for the expression of pro-and anti-inflammatory mediators including TNF-α, IL-1, IL-2, IL-6, IL-8, IL-10, IL-23, IFN-γ, iNOS, and COX-2 [8,404]. The most implicated signal transduction pathways involved in orchestrating inflammatory response are NF-κB, MAPK, signal transducer and activator of transcription (STAT) and Toll-like receptor (TLR) signaling [8,405]. Docking studies showed that αT3 blocks the assess of arachidonic acid to the catalytic site of 12-lipoxygenase, thereby achieving its anti-inflammatory effects [406].…”
Section: Anti-inflammatory Properties Of Tocotrienolmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin E is an essential lipid-soluble vitamin that consists of two subgroups: tocopherol and tocotrienol (Wong et al, 2019). Due to presence of tocotrienol, there is an improve in proliferation, differentiation, and mineralization, and reduced apoptosis of osteoblastic cells (Abd Manan, Mohamed, & Shuid, 2012)and (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular-based treatment strategies for osteoporosis including current molecular and genetic opinions on osteoporosis and its medical treatment are reviewed by two research groups [11,12]. Wong and colleagues detail how the molecular actions of vitamin E regulate the bone remodeling cycle [13], while Rossi and colleagues discuss the endocannabinoid/endovanilloid system only in osteoporosis and also in bone cancer treatment [14]. Finally, Chin and colleagues review the evidence on the functional food component, tocotrienol, which they suggest may be used to prevent male osteoporosis [15].…”
mentioning
confidence: 99%